A Review of John Rawls’ Theory of Justice on the Implementation of Restorative Justice Through Penal Mediation in Indonesia - Ahmad Wildan Rofrofil Akmal; Siti Nur Syifa; Erfaniah Zuhriah (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstracts: This study examines the implementation of restorative justice through the mechanism of penal mediation within Indonesia's criminal justice system, using John Rawls’ theory of justice as a theoretical framework. The research is grounded in the need for a more humane, participatory, and efficient alternative for resolving minor criminal offenses, as opposed to the conventional retributive justice system. This is a normative legal study employing both statutory and conceptual approaches. The data sources consist of primary and secondary legal materials obtained through literature review. The findings reveal that penal mediation has been applied in cases such as petty theft, defamation, and domestic violence, involving offenders, victims, families, and the community in the restorative process. This implementation reflects Rawls’ principles of justice particularly the equal basic liberties and the difference principle—in protecting vulnerable groups such as juvenile offenders and first-time offenders. In conclusion, penal mediation aligns not only with restorative justice values and the Islamic legal concept of maslahah, but also embodies a substantive model of justice that is inclusive and responsive to local values. Therefore, this approach deserves to be formally institutionalized within the national criminal law system.Keywords: Penal mediation, restorative justice, John Rawls’ theory of justice, Indonesian criminal law, non-litigation resolution.Abstrak : Penelitian ini mengkaji penerapan keadilan restoratif melalui mekanisme mediasi penal dalam sistem peradilan pidana Indonesia, dengan menggunakan perspektif teori keadilan John Rawls. Latar belakang penelitian ini berangkat dari kebutuhan untuk menghadirkan alternatif penyelesaian perkara pidana ringan yang lebih manusiawi, partisipatif, dan efisien dibandingkan sistem peradilan konvensional yang cenderung retributif. Penelitian ini merupakan studi hukum normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Sumber data diperoleh dari bahan hukum primer dan sekunder melalui studi kepustakaan. Hasil penelitian menunjukkan bahwa mediasi penal telah diterapkan dalam sejumlah kasus seperti pencurian ringan, penghinaan, dan kekerasan rumah tangga, dengan melibatkan pelaku, korban, keluarga, dan masyarakat dalam proses pemulihan. Implementasi ini mencerminkan prinsip keadilan Rawls, yaitu kebebasan dasar yang setara dan prinsip perbedaan, khususnya dalam melindungi pelaku dari kelompok rentan seperti anak dan pelaku pertama. Kesimpulannya, mediasi penal bukan hanya sejalan dengan nilai-nilai keadilan restoratif dan maslahah dalam hukum Islam, tetapi juga mencerminkan prinsip keadilan substantif yang inklusif dan adaptif terhadap nilai lokal. Oleh karena itu, pendekatan ini layak untuk dilembagakan secara normatif dalam sistem hukum pidana nasional.Kata kunci: Mediasi penal, keadilan restoratif, teori keadilan John Rawls, hukum pidana Indonesia, penyelesaian non-litigasi.